Ferritic free-cutting stainless steel with excellent precision cutting properties
Patent Information
- Application Number
- JP2021041271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-03-15
AI Technical Summary
Existing ferritic stainless steels fail to adequately suppress built-up edges and achieve smooth cutting surface properties, particularly in high-corrosion environments, despite previous attempts to improve machinability with boron and other additives.
A finely controlled composition and heat treatment process involving nitrogen and boron nitride compounds, with specific element limits and annealing conditions, to suppress built-up edges and enhance cutting tool life and surface smoothness.
The solution provides a ferritic stainless steel with excellent tool life and smooth cutting surfaces, suitable for precision parts in corrosive environments, by finely dispersing boron nitride compounds and controlling nitrogen content.
Abstract
Description
[Technical Field]
[0001] This invention relates to a ferritic stainless steel that exhibits excellent precision machinability and suppresses the formation of built-up edge, for use in cutting small parts that require corrosion resistance. [Background technology]
[0002] Ferritic stainless steel is used in precision equipment parts requiring durability due to its corrosion resistance and low thermal expansion coefficient. In particular, in precision equipment parts machined from polished rods, it is often used in rotating parts, requiring especially precise machinability. Specifically, it is required to have excellent tool life during machining and an extremely smooth cut surface without built-up edge detachment marks. Built-up edge is a deposit that forms and grows on the cutting tool tip due to adhesion of the base material, and when it detaches from the tool tip during machining, it is pressed onto the cut surface and deteriorates the surface properties.
[0003] To date, in highly corrosion-resistant ferritic stainless steel, there has been a proposal for a ferritic free-cutting stainless steel that has machinability comparable to that of lead (Pb) by adding B and controlling the ratio of oxygen to B to precipitate B-containing oxide inclusions (Patent Document 1).
[0004] Furthermore, there is a proposal for ferritic free-cutting stainless steel in which boron nitride particles are dispersed at a concentration of 0.1% or more as an alternative to Pb or MnS cutting particles (Patent Document 2). It has also been proposed to add B to austenitic stainless steel to which a free-cutting agent has been added, thereby uniformly dispersing h-BN (hexagonal boron nitride) particles in the steel to impart machinability (Patent Document 3).
[0005] Furthermore, a ferritic free-cutting stainless steel has been proposed in which B and N are added to ferritic stainless steel with S added as a substitute for Pb, and the size and number density of intermetallic compounds containing B, N, and S are controlled (Patent Document 4). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2008-274361 [Patent Document 2] Japanese Patent Publication No. 2003-129191 [Patent Document 3] Patent No. 5142289 [Patent Document 4] Patent No. 5957241 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] Patent documents 1 to 4 do not adequately suppress built-up edge marks, and the problem of achieving a smooth cutting surface remains unresolved, thus presenting issues from the viewpoint of achieving a precise cutting surface.
[0008] The present inventors have found that, with the known techniques or combinations described in the background art above, it is not possible to achieve both excellent tool life and excellent smooth surface properties with suppressed built-up edge marks in highly corrosion-resistant ferritic free-cutting stainless steel that provides excellent machinability.
[0009] The problem to be solved by the present invention is to provide a highly corrosion-resistant ferritic free-cutting stainless steel for use in precision parts made of ferritic stainless steel used in harsh, corrosive environments where precision is required, which exhibits excellent tool life during machining and provides a cut surface with excellent flatness during machining. [Means for solving the problem]
[0010] To solve the above problems, the inventors conducted various studies on sulfur-containing ferritic free-cutting stainless steel and found that by adding B and N to the sulfur-containing free-cutting element system, and controlling the amount of dissolved N by finely precipitating BN through N-solution softening treatment, it is possible to suppress built-up edge marks during precision cutting and obtain a surface with excellent smoothness during cutting.
[0011] This invention is based on the above findings, and its gist is as follows.
[0012] (1) The chemical composition is as follows, by mass%, containing C: less than 0.10%, Si: 0.1-2.0%, Mn: 0.1-3.0%, S: 0.02-0.40%, P: 0.10% or less, Cr: 13.0-22.0%, B: 0.001-0.01%, N: 0.015-0.08%, Al: 0.008% or less, and O: 0.015% or less, with the remainder being Fe and impurities, with a solid-solution N content of 0.010-0.060%, and containing 100 μm of BN-based intermetallic compounds of 0.5 μm or less. 2 A ferritic free-cutting stainless steel characterized by having 20 or more particles inside.
[0013] (2) The ferritic free-cutting stainless steel of (1), characterized in that, in place of a portion of the Fe, it further contains one or more of the following in mass%, in amounts of Ni: 1.5% or less, Mo: 2.5% or less, Cu: 1.5% or less, Co: 1.5% or less, and W: 2.5% or less.
[0014] (3) The ferritic free-cutting stainless steel according to (1) or (2) above, characterized in that, in place of a portion of the Fe, it further contains one or more of the following in mass%, in the following amounts: Bi: 0.20% or less, Sn: 0.30% or less, Sb: 0.30% or less, Ag: 0.30% or less, and Te: 0.10% or less.
[0015] (4) A ferritic free-cutting stainless steel according to any of (1) to (3) above, characterized in that, in place of a portion of the Fe, it further contains one or more of the following in mass%, in the following amounts: V: 0.8% or less, Nb: 0.5% or less, Ti: 0.5% or less, and Ta: 0.5% or less.
[0016] (5) A ferritic free-cutting stainless steel according to any of (1) to (4) above, characterized in that, in place of a portion of the Fe, it further contains one or more of the following in mass%, in the following amounts: Mg: 0.010% or less, Ca: 0.010% or less, Hf: 0.010% or less, and REM: 0.050% or less.
[0017] (6) A heating step of heating a slab having any one of the chemical components (1) to (5) to 1150 to 1330 °C, a processing step of performing hot rolling or hot working on the heated slab, a batch annealing step of holding at 700 to 900 °C for 60 to 300 minutes, and a strand annealing of holding in a temperature range of 700 to 900 °C and cooling at a cooling rate of 1 °C / s or more. A method for producing a ferritic free-cutting stainless steel according to the present invention, characterized by comprising the above steps.
Effects of the Invention
[0018] According to the present invention, in ferritic free-cutting stainless steel, by performing appropriate component adjustment and heat treatment for controlling the metal structure and intermetallic compounds, excellent flat cutting surface properties with good cutting tool life and suppressed formation of built-up edge marks can be obtained, and a material suitable for precision parts with excellent corrosion resistance is provided.
Embodiments for Carrying Out the Invention
[0019] Each requirement of the present invention will be described below. In the following description, “%” is “mass %” unless otherwise specified.
[0020] 《Essential Component Composition of Steel》 The high-corrosion-resistance ferritic free-cutting stainless steel of the present invention is generally targeted at parts that require durability and a low coefficient of thermal expansion, and is based on high-corrosion-resistance ferritic stainless steel.
[0021] C can be contained less than 0.10% in order to ensure the strength of the base metal. However, when 0.10% or more is added, a large amount of Cr carbide is generated, not only deteriorating the corrosion resistance, but also deteriorating the cutting surface properties and tool life. Therefore, it is limited to less than 0.10%. Preferably, it is 0.08% or less.
[0022] N is added at a concentration of 0.015% to obtain a BN-based intermetallic compound through the N solid solution softening treatment described later, and to ensure sufficient solid-solution N to suppress the formation of built-up edge marks. However, if the concentration exceeds 0.08%, not only will corrosion resistance deteriorate due to Cr nitrides, but the cutting surface properties will also deteriorate. Therefore, it is limited to 0.08% or less. Preferably, it is in the range of 0.02 to 0.06%.
[0023] Si is included at a concentration of 0.1% or more to suppress the formation of coarse inclusions that deoxidize and degrade the cutting surface properties. However, if the concentration exceeds 2.0%, it hardens and promotes adhesion of the base material to the tool, thus encouraging the formation of built-up edge marks. Therefore, it is limited to 2.0% or less. Preferably, it is in the range of 0.2 to 1.0%.
[0024] Mn is included at a concentration of 0.1% or more to suppress the formation of coarse inclusions that degrade the cutting surface properties through deoxidation, and to ensure good tool life by forming sulfides. However, if the concentration exceeds 3.0%, hardening occurs due to solid solution hardening, degrading tool life. Therefore, it is limited to 3.0% or less. Preferably, it is in the range of 0.2 to 2.0%.
[0025] S is added at a concentration of 0.02% or more to form sulfides and ensure good tool life. However, if the concentration exceeds 0.40%, the formation of built-up edge marks on the tool during precision cutting becomes significant, and it becomes impossible to prevent the detachment of built-up edge marks from the cutting surface. Therefore, it is limited to 0.40% or less. Preferably, it is in the range of 0.03 to 0.30%.
[0026] Although phosphorus (P) is inevitably introduced as an impurity from the raw materials, if its content exceeds 0.10%, it not only deteriorates corrosion resistance due to grain boundary segregation but also significantly reduces manufacturability. Therefore, its content should be limited to 0.10% or less. Preferably, it should be 0.05% or less.
[0027] Cr is included in a concentration of 13.0% or more to obtain the corrosion resistance function of stainless steel and to acquire a ferrite structure with a low coefficient of thermal expansion and good machinability. However, if the concentration exceeds 20.0%, severe sticking with the tool occurs, making it impossible to ensure the cutting surface properties. Therefore, it is limited to 22.0% or less. Preferably, it is between 15.0% and 20.0%.
[0028] When added together with N, B forms fine BN during the N solid solution softening treatment, suppressing adhesion of the base material to the tool surface and preventing built-up edge marks on the cutting surface. Therefore, it is added at a concentration of 0.001% or more. However, adding more than 0.0100% generates coarse boride, which not only promotes the formation of built-up edge but also significantly degrades manufacturability. Therefore, it is limited to 0.0100% or less. Preferably, it is between 0.0020% and 0.0070%.
[0029] Al may be added for deoxidation, but if the content exceeds 0.008%, coarse inclusions will form and the surface properties will deteriorate. Therefore, it should be limited to 0.008% or less. Preferably, it should be 0.006% or less.
[0030] O is an unavoidable impurity, but if it is present in amounts exceeding 0.015%, coarse inclusions are formed, degrading the cutting surface properties. Therefore, it should be limited to 0.015% or less. Preferably, it should be 0.012% or less.
[0031] The amount of dissolved nitrogen in the ferritic free-cutting stainless steel of the invention is 0.01 to 0.06%.
[0032] Solid-solution nitrogen (N) in the ferrite matrix is effective in embrittlement of the base material during cutting, suppressing the formation of built-up edge and obtaining good surface properties. Therefore, the amount of solid-solution nitrogen is limited to 0.01% or more. However, if the amount of solid-solution nitrogen exceeds 0.060%, it has the opposite effect and actually deteriorates tool life. Therefore, the upper limit of the amount of solid-solution nitrogen was set to 0.06%. In this invention, as described later, nitrogen is solid-solutioned into the ferrite matrix by strand annealing (rapid cooling).
[0033] The microstructure of the ferritic free-cutting stainless steel of the present invention is composed of BN-based intermetallic compounds of 0.5 μm or less, up to 100 μm. 2 Contains 20 or more.
[0034] BN is effective in preventing the formation of built-up edges and achieving excellent cutting surface properties by suppressing adhesion of the base material to the tool through its self-lubricating action. However, if coarse BN exceeding 0.5 μm in size is dispersed, the plastically deformed base material and BN will layer and accumulate at the tool tip, generating and growing built-up edges. Therefore, fine dispersion of BN with a major diameter of 0.5 μm or less is used to suppress layering and accumulation. 2 The effect becomes more pronounced when BN is finely dispersed within the material at a number density of 20 or more particles. Preferably, 100 μm 2 There are more than 30 inside.
[0035] Selectively selected ingredients The stainless steel of the present invention is composed of chemical components consisting of Fe and impurities, in addition to the elements described above. Furthermore, in addition to the above component composition, the following elements may be selectively included in place of a portion of the Fe.
[0036] The elements Ni, Cu, and Co do not necessarily need to be added. Adding them improves the corrosion resistance and toughness of the product. However, adding more than 1.5% makes the material less supple during annealing, thus degrading tool life. Therefore, the content should be 1.5% or less. To reliably obtain the above effects, it is preferable that the content of each element be between 0.01% and 1.0%.
[0037] The elements Mo and W do not need to be added. Degradation of these elements improves the corrosion resistance of the product. However, if added in amounts exceeding 2.5%, the effect saturates and, conversely, degrades the tool life during machining. Therefore, the content should be 2.0% or less. To reliably obtain the above effects, it is preferable that the content of each element be between 0.01% and 2.0%.
[0038] The element Bi does not necessarily need to be added. If added, it acts as a self-lubricating agent during cutting, suppressing the formation of built-up edge and improving the cutting surface properties. However, if added in amounts exceeding 0.20%, the hot workability deteriorates significantly, making manufacturing impossible. Therefore, the content should be 0.20% or less. To reliably obtain the above effects, it is preferable that the content of each element be between 0.01% and 2.0%.
[0039] The elements Sn, Sb, and Ag do not necessarily need to be added. If added, they act as a self-lubricating agent during cutting, suppressing the formation of built-up edge and improving the cutting surface properties. However, if added in amounts exceeding 0.30%, the hot workability deteriorates significantly, making manufacturing impossible. Therefore, the content should be 0.30% or less. To reliably obtain the above effects, it is preferable to have a content of 0.005% or more and 0.20% or less.
[0040] The element Te does not necessarily need to be added. If added, it generates spherical sulfides, which suppress the accumulation and growth of built-up edges and improve the cutting surface properties. However, if added in amounts exceeding 0.10%, the hot workability deteriorates significantly, making manufacturing impossible. Therefore, the content should be 0.10% or less. To reliably obtain the above effect, it is preferable to have a content of 0.005% or more and 0.05% or less.
[0041] The element V does not need to be added. Adding it improves the corrosion resistance of the product. However, if added in amounts exceeding 0.8%, coarse carbonitrides are formed, promoting the stacking and growth of built-up edges, degrading the cutting surface properties, and reducing tool life. Therefore, the upper limit should be 0.8% or less. To reliably obtain the above effects, it is preferable to have a content of 0.05% or more and 0.5% or less.
[0042] The elements Nb, Ti, and Ta do not necessarily need to be added. Adding them improves the corrosion resistance of the product. However, adding more than 0.5% can lead to the formation of coarse carbonitrides, promoting the accumulation and growth of built-up edges, degrading the cutting surface properties, and reducing tool life. Therefore, the upper limit should be 0.5% or less. To reliably obtain the above effects, it is preferable to have a content of 0.01% or more and 0.4% or less.
[0043] The elements Mg, Ca, and Hf do not necessarily need to be added. Adding them improves hot workability. However, adding more than 0.010% of each element saturates the effect and, conversely, generates coarse oxides, degrading the surface properties of the machined material. Therefore, the content should be 0.010% or less. To reliably obtain the above effect, it is preferable to have a content of 0.001% or more and 0.005% or less.
[0044] The addition of REM elements is optional. Adding them improves hot workability. However, adding more than 0.050% saturates the effect and conversely generates coarse oxides, degrading the cutting surface properties. Therefore, the content should be 0.050% or less. To reliably obtain the above effect, it is preferable to have a content of 0.001% or more and 0.005% or less. REM (rare earth elements), according to the general definition, refers to the two elements scandium (Sc) and yttrium (Y), and the 15 elements from lanthanum (La) to lutetium (Lu) (lanthanoids). They may be included individually or as a mixture.
[0045] Typical impurities contained in the stainless steel of the present invention include Zn, Pb, Ge, Se, Ag, and Se, which are usually introduced as impurities in the steel manufacturing process in a range of about 0.1%.
[0046] Oxygen, an impurity, mainly exists as an inclusion in steel, but the oxygen content level of stainless steel produced by normal refining is 0.001 to 0.015%.
[0047] Furthermore, while representative optional additive elements are specified in (2) to (5) above, elements not listed in this specification may also be included as long as they do not impair the effects of the present invention.
[0048] Manufacturing method for ferritic stainless steel The present invention describes a method for producing ferritic stainless steel.
[0049] BN particles smaller than 0.5 μm in size, 100 μm 2 In order to achieve fine dispersion of 20 or more particles within the material, the cast slab containing the above-mentioned components is first heated to a high temperature of 1150-1330°C, then hot-rolled or hot-worked to dissolve the BN. After that, the resulting steel material (wire rod, steel wire, etc.) is subjected to batch annealing at 700-900°C for 60-300 minutes.
[0050] If the heating temperature of the cast slab is below 1150°C, BN will not dissolve completely, and the aforementioned number density will not be met. If the temperature exceeds 1330°C, the manufacturability deteriorates. Therefore, the heating temperature should be between 1150°C and 1330°C, and furthermore, from the perspective of BN solid dissolution, it should be between 1250°C and 1320°C.
[0051] Furthermore, if the batch annealing temperature is lower than 700°C and the annealing time is shorter than 60 minutes, the amount of BN precipitated decreases, and the number density described above is no longer satisfied. On the other hand, if the batch annealing temperature is higher than 900°C and the annealing time is longer than 300 minutes, the BN size becomes coarser, and the number density described above is no longer satisfied. For this reason, the batch annealing conditions are limited to 700-900°C with a holding time of 60-300 minutes, preferably 100-250 minutes.
[0052] In order to maintain the dispersion state of BN described above while ensuring a sufficient amount of solid-solution N in the ferrite, after the batch annealing described above, strand annealing is performed by holding the material at a temperature range of 700 to 900°C and then cooling it at a cooling rate of 1°C / s or more in a temperature range of 500°C or higher.
[0053] In typical softening annealing of ferritic stainless steel, the entire coil, such as wire or steel wire, is held at a temperature range of approximately 650-950°C during batch annealing and then furnace-cooled, resulting in slow cooling at a cooling rate of, for example, on the order of 0.02°C / s. Since the nitrogen (N) that was dissolved at high temperatures changes its state of existence to nitride during slow cooling, the amount of dissolved N in typical batch annealing is less than 0.01%.
[0054] In the present invention, after the aforementioned annealing, strand annealing is performed, in which the ferrite phase is held in a temperature range of 700 to 900°C where the N solid solubility limit is 0.01 to 0.06% and BN does not solid dissolve, and then rapidly cooled at a temperature range of 500°C or higher where nitrides are formed at a rate of 1°C / s or higher. This makes it possible to maintain the N solid solubility in the ferrite phase at 0.01 to 0.06% while preserving the fine dispersion state of BN.
[0055] Strand annealing is an annealing method in which a ring-shaped wire or steel wire coil is unfolded into a straight line and subjected to short-time heat treatment (in an atmosphere of nitrogen, Ar, or ammonia decomposition gas, etc.), followed by air cooling or indirect air cooling. This method allows for a significantly faster cooling rate compared to batch annealing of the entire ring-shaped coil.
[0056] At this time, if the holding temperature is below 700°C, the amount of dissolved nitrogen will be less than 0.01%, and if it is above 900°C, an austenite phase will form, and a hard martensitic structure will be formed during cooling, resulting in insufficient machinability (cutting surface properties, tool life) as described above. For this reason, the strand annealing temperature is limited to the range of 700 to 900°C. Preferably, it is 750 to 850°C. The furnace time is arbitrary, but a range of 30 to 1000 s is preferable because it allows for uniform heating without thermal deformation of the material.
[0057] Furthermore, it is acceptable to include processes such as cold drawing between the batch annealing and strand annealing steps mentioned above. Batch annealing and strand annealing may be performed multiple times, but the final heat treatment must be strand annealing.
[0058] As described above, the present invention provides a ferritic free-cutting stainless steel that can suppress the formation and growth of built-up edges, which degrade the surface properties of the machined surface during precision machining, for use in precision parts with a low coefficient of thermal expansion that are precisely machined. [Examples]
[0059] (Example 1) Steel with the chemical compositions shown in Tables 1 and 2 was melted at 1600°C in a 65kg vacuum melting furnace and then cast into a mold. After heating to 1200°C, it was hot-worked into φ9mm wire and subjected to batch annealing at 850°C for 120 minutes, followed by cold drawing to φ6.3mm, and then strand annealing (in ammonia decomposition gas) at 850°C for 200 seconds. Finally, it was drawn into a polished bar to φ6.0mm using a drawing machine and used as a material for cutting.
[0060] [Table 1]
[0061] [Table 2]
[0062] The bar stock obtained in this manner was evaluated for the number density (number of BN compounds per unit area), surface properties after outer circumference cutting, and tool life using the evaluation method described below. The results are shown in Tables 3 and 4. Table 3 shows the evaluation results for the steel of the present invention, and Table 4 shows the evaluation results for the comparative steel.
[0063] [Table 3]
[0064] [Table 4]
[0065] "Intermetallic compounds (BN compounds)" A longitudinal section of a wire embedded in resin and mirror-polished was electrolytically extracted using an alcohol-based etching solution. A replica sample was then prepared by carbon deposition, and the size and distribution of the precipitates were investigated using a transmission electron microscope. (100 μm) 2 The area was observed in 5 fields of view, and the 100 μm BN compound with a major axis of 0.5 μm or less was measured. 2 The number density inside was calculated.
[0066] "Cutting surface properties" Under the conditions of precision cutting with a feed rate of 0.05 mm / rev. or less, using a carbide P-type tool, a cutting edge radius of 0.4 mm, a cutting speed of 50 m / min, a feed rate of 0.02 mm / rev., a depth of cut of 0.1 mm, and cutting fluid (mineral oil), the outer circumference of a wire was cut in the circumferential direction. The surface after cutting was observed with a 100x magnifying glass and evaluated for the presence or absence of clear built-up edge marks. Clear built-up edge marks were marked with ×, minute built-up edge marks were scattered with ○, and no clear built-up edge marks were marked with ◎.
[0067] "Tool life" The tool used was a carbide P-type, with a cutting edge radius of 0.4 mm. The cutting speed was 200 m / min, the feed rate was 0.02 mm / rev., the depth of cut was 0.11 mm, and cutting fluid (mineral oil) was used. Under the conditions of precision cutting with a feed rate of 0.05 mm / rev. or less and a depth of cut of ≤ 0.3 mm, the outer circumference of a wire rod was cut in the circumferential direction for 30 minutes. The condition of the tool after use was examined. The flank wear of the tool after use, including boundary wear and streaky wear, was evaluated as follows: ◎ if it was 20 μm or less, ○ if it was more than 20 μm but 50 μm or less, and × if it was more than 50 μm.
[0068] "Solute N amount" One g of the material was electrolyzed in maleic anhydride, and the precipitate was extracted using a 0.2 μm mesh filter paper. After dissolving the extract in an acid solution, the amount of nitrogen precipitated as nitride in the precipitate was determined by atomic absorption spectrometry. The amount of dissolved nitrogen was then calculated by subtracting the amount of nitrogen in the precipitate from the total nitrogen content of the steel.
[0069] Examples 1 to 43 of the present invention in Table 3 have a number density of BN with a major axis of 0.5 μm or less of 100 μm 2Among the 20 or more, the amount of dissolved N is 0.01 to 0.06%, and all of them exhibit excellent cutting surface properties and tool life.
[0070] On the other hand, Comparative Examples 1 to 9, 11 to 33 in Table 4 are outside the component range, BN number density range, and dissolved N amount range of the present invention, and could not satisfy all of the excellent cutting surface properties and tool life. Comparative Example 10 had a small Cr amount, and the BN number density range, material hardness range, and dissolved N amount range were within the scope of the present invention. Although the cutting surface properties and tool life were also excellent, the corrosion resistance was insufficient.
[0071] (Example 2) Regarding Steel A melted at 1600°C in a 65 kg vacuum melting furnace and cast into a mold, after heating at 1100 to 1360°C, it was hot-rolled into a φ9 mm wire rod, softened and annealed at 650 to 1000°C for 30 to 500 minutes, cold-drawn to φ6.3 mm, and strand annealing (in ammonia-decomposed gas) was performed at 650 to 950°C for 30 to 1500 s. Then, it was finished to a grinding rod with a drawbench to φ6.0 mm as a material for finish cutting. Thereafter, evaluations were carried out on the number density of the BN compound (number per unit area), the surface properties after outer peripheral cutting, and the tool life. The results are shown in Table 5.
[0072]
Table 5
[0073] In Examples 44 to 51 of Table 5, the number density of BN with a major axis of 0.5 μm or less is 100 μm 2 Among the 20 or more, the amount of dissolved N is 0.01 to 0.06%, and all of them exhibited excellent cutting surface properties and tool life.
[0074] On the other hand, Comparative Examples 34 to 41 in Table 5 are outside the component range, BN number density range, and dissolved N amount range of the present invention, and could not satisfy all of the excellent cutting surface properties and tool life.
Industrial Applicability
[0075] As is clear from the above embodiments, the present invention provides a ferritic free-cutting stainless steel with excellent flatness of the cutting surface and tool life during precision cutting, significantly improving the durability of precision parts with low thermal expansion coefficients in corrosive environments, and is extremely useful in industry.
Claims
1. In mass%, C: less than 0.10% Si: 0.1-2.0%, Mn: 0.1 to 3.0%, S: 0.02-0.40%, P: 0.10% or less, Cr: 13.0-22.0%, B: 0.001-0.01%, N: 0.015-0.08%, Al: 0.008% or less, and O: 0.015% or less and the balance being Fe and impurities, The amount of solute N is 0.010 to 0.060%, BN-based intermetallic compounds of 0.5 μm or less are 100 μm 2 There are more than 20 in A ferritic free-cutting stainless steel characterized by:
2. Part of the Fe is replaced with further mass% Ni: 1.5% or less, Mo: 2.5% or less, Cu: 1.5% or less, Co: 1.5% or less, and W: 2.5% or less Contains one or more of the following:
2. The ferritic free-cutting stainless steel according to claim 1.
3. Part of the Fe is replaced with further mass% Bi: 0.20% or less, Sn: 0.30% or less, Sb: 0.30% or less, Ag: 0.30% or less, and Te: 0.10% or less Contains one or more of the following:
3. The ferritic free-cutting stainless steel according to claim 1 or 2.
4. Part of the Fe is replaced with further mass% V: 0.8% or less, Nb: 0.5% or less, Ti: 0.5% or less, and Ta: 0.5% or less Contains one or more of the following: The ferritic free-cutting stainless steel according to any one of claims 1 to 3.
5. Part of the Fe is replaced with further mass% Mg: 0.010% or less, Ca: 0.010% or less, Hf: 0.010% or less, and REM: 0.050% or less Contains one or more of the following: The ferritic free-cutting stainless steel according to any one of claims 1 to 4.
6. A heating step of heating a cast having the chemical composition according to any one of claims 1 to 5 to 1150 to 1330 ° C.; a processing step of hot rolling or hot working the heated slab; Batch annealing process at 700-900°C for 60-300 minutes; Strand annealing is performed by holding the temperature in the range of 700 to 900°C and cooling at a rate of 1°C / s or more. The method for producing ferritic free-cutting stainless steel of the present invention comprises: